2017
DOI: 10.3389/fpls.2017.00813
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Locus Analysis for Deep-Sowing Germination Ability in the Maize IBM Syn10 DH Population

Abstract: Deep-sowing is an effective measure to ensure seeds absorbing water from deep soil layer and emerging normally in arid and semiarid regions. However, existing varieties demonstrate poor germination ability in deep soil layer and some key quantitative trait loci (QTL) or genes related to deep-sowing germination ability remain to be identified and analyzed. In this study, a high-resolution genetic map based on 280 lines of the intermated B73 × Mo17 (IBM) Syn10 doubled haploid (DH) population which comprised 6618… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 42 publications
5
29
0
Order By: Relevance
“…e ∕ r + S 2 e × 100, where S 2 t : treatment variance; S 2 e : error variance; r: the number of replicates (Liu et al, 2017).…”
Section: Histograms Of Frequency Distributions Of Germination-relatedmentioning
confidence: 99%
See 1 more Smart Citation
“…e ∕ r + S 2 e × 100, where S 2 t : treatment variance; S 2 e : error variance; r: the number of replicates (Liu et al, 2017).…”
Section: Histograms Of Frequency Distributions Of Germination-relatedmentioning
confidence: 99%
“…The study of Qin, Zhao, Yang, Li, and Yang (2018) showed that it could improve the yield traits in the case of maize variety 'Zhongyu 3' by increasing sowing depth properly. However, the existing varieties of maize have poor deep-sowing tolerance during seed germination (Kalpana et al, 2015;Liu et al, 2017;Troyer, 1997;Yin et al, 2016;Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Vigorous and uniform seedlings are necessary for achieving a high yield in crop production. However, various abiotic stresses occurring after sowing impair seedling establishment ( Basnet et al, 2015 ; Liu et al, 2017 ). Maize ( Zea mays L.) is one of the most important crops, accounting for 40% of the world’s cereal food production ( Bouis and Welch, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a significant number of recombination events, generating this population is very labor-and time-intensive. Recently, an IBM-DH population was developed and used in a deep-sowing germination quantitative trait loci (QTL) study [14]. Compared with populations generated by DH induction in early generations, the IBM-DH population is relatively fast and cost-effective to generate, while enhancing QTL mapping resolution.…”
Section: Introductionmentioning
confidence: 99%